Strategies for industrialisation : the case of Bangladesh - Huq, M. M.; Love, Jim, 1948- (Dhaka : University Press, 2000)
Collection of papers presented at a series of conferences.
Machine generated contents note: Chapter 1 -- BANGLADESH INDUSTRIALISATION SINCE INDEPENDENCE -- Mozammel Huq and Jim Love -- Chapter 2 -- EXTERNAL COMPETITIVENESS AND ECONOMIC DEVELOPMENT 25 -- Jim Love -- Chapter 3 -- INDUSTRIALISATION, INDUSTRIAL POLICY AND GLOBAL -- COMPETITIVENESS 45 -- Frederick Nixson -- Chapter 4 -- INDUSTRIAL DEVELOPMENT IN A CHANGING GLOBAL ECONOMY 63 -- John Henley and Colin Kirkpatrick -- Chapter 5 -- TRADE LIBERALISATION, EXPORTS AND GROWTH OF -- MANUFACTURIONG INDUSTRIES IN BANGLADESH 87 -- Zaid Bakht -- Chapter 6 -- EXCIIANGE RATE FUNDAMENTALS, MISALIGNMENT, AND -- ECONOMIC PERFORMANCE: BANGLADESH IN THE -- SOUTH ASIAN CONTEXT 123 -- Mohammad Yunus -- Chapter 7 -- EXPORT PROMOTION THROUGH EXPORT INCENTIVES: THE -- BANGLADESH INCENTIVE REGIME IN A REGIONAL CONTEXT 153 -- Mustafizur Rahman -- Chapter 8 -- TECHNOLOGY POLICY FOR INDUSTRIALISATION IN A DEVELOPING COUNTRY: THE CASE OF BANGLADESH 195 -- Mozammel Huq -- Chapter 9 -- INTERSECTORAL LINKAGES IN BANGLADESH 225 -- Mohammed Salimullah, Mozammel Huq and lain McNicoll -- Chapter 10 -- EXPORT COMPETITIVENESS OF BANGLADESH LEATHER MANUFACTURING: A POLICY SUCCESS? 279 -- Mozammel Huq -- Chapter II -- EMERGENCE AND GROWTH OF THE RMG SECTOR IN BANGLADESH 303 -- Debapriya Bhattacharya.
Includes bibliographical references and index.
Keywords: Industrialization -- Bangladesh -- Congresses; Industrial policy -- Bangladesh -- Congresses; Industrial promotion -- Bangladesh -- Congresses